27th European Mask and Lithography Conference 2011
DOI: 10.1117/12.896911
|View full text |Cite
|
Sign up to set email alerts
|

Effective EUVL mask cleaning technology solutions for mask manufacturing and in-fab mask maintenance

Abstract: Extreme Ultraviolet Lithography (EUVL) is considered the leading lithography technology choice for semiconductor devices at 16nm HP node and beyond. However, before EUV Lithography can enter into High Volume Manufacturing (HVM) of advanced semiconductor devices, the ability to guarantee mask integrity at point-of-exposure must be established. Highly efficient, damage free mask cleaning plays a critical role during the mask manufacturing cycle and throughout the life of the mask, where the absence of a pellicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…And type II has a Ta based absorber layer on a 100-nm-thick Ru bulk layer as shown in Fig. 12,17,20,21 The electron trajectories inside and outside these samples were simulated using CHARIOT MONTE CARLO software (Abeam Technologies, Inc.). The detail structure of the Ta based absorber layer was described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…And type II has a Ta based absorber layer on a 100-nm-thick Ru bulk layer as shown in Fig. 12,17,20,21 The electron trajectories inside and outside these samples were simulated using CHARIOT MONTE CARLO software (Abeam Technologies, Inc.). The detail structure of the Ta based absorber layer was described earlier.…”
Section: Methodsmentioning
confidence: 99%
“…Because the reticles do not have a pellicle anymore, as was the modus operandi for visible light lithography, cleanliness is becoming critical for the application of EUVL. Wet cleaning of reticles is also under research and results looks promising [4] . However, a dry cleaning technology for rapid removal of organic contamination might be favorable for in-fab cleaning as this has a relatively short cycle time.…”
Section: Carbon Removal From Reticlesmentioning
confidence: 99%
“…7,8 However, the mask structure should be taken into account when dealing with the mask fabrication processes, such as patterned mask inspection, 9-13 critical dimension measurement (CD metrology), 14,15 mask repair, 16,17 and cleaning. 18 Takai et al reported that the reduction of the ML stack down to 20 pairs effectively avoided the collapse of the lines by the cleaning process. 19 However, patterned mask inspection, CD metrology, and repair of this mask structure continue to pose challenges that need to be addressed.…”
Section: Introductionmentioning
confidence: 99%